THE ROLE OF WORK ENGAGEMENT, CAREER DEVELOPMENT AND SELF-EFFICACY ON NURSES TURNOVER INTENTION MEDIATED BY JOB SATISFACTION IN CILACAP XYZ PRIVATE HOSPITAL, CENTRAL JAVA - Oktavia, Ines Marcelina; Yohana Cahaya F. Palupi Meilani (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2024)
Based on data obtained from XYZ Private Hospital in Cilacap from 2021, 2022 and 2023, it was found that there were quite high turnover rates of 21.6%, 25% and 5.26%. Even though the percentage will decrease in 2023, this figure is still a high number because it can have an impact on hospital management so it needs further attention. This research uses a cross-sectional method to obtain quantitative data from questionnaires distributed online. The questions in the questionnaire are modifications of questionnaire questions obtained from previous literature. Data collected from a population of medical personnel who had worked at the XYZ private hospital in the city of Cilacap, Central Java for one year using non-probability sampling techniques. This research uses PLS-SEM to analyze and process the data that has been collected. This research aims to analyze the factors that cause turnover among health workers in hospitals, as well as to determine the influence of work engagement, career development, self-efficacy on turnover intention. mediated by job satisfaction.